Mesh migration and vesicocutaneous fistula development following totally extra-peritoneal hernia repair - Özçelik, Mehmet Faik; Orhan, Orhan; Erginöz, Ergin; Çarkman, Sinan (Cerrahpaşa Medical Journal, 2023)
Introduction: Totally extra-peritoneal (TEP) inguinal hernia repair is a minimally invasive procedure that is safe and efficacious as open hernia repair. Despite advancements in technology, the presence of mesh inside the abdomen poses a risk for the development of complications during the post-operative period such as mesh migration, mesh infection, and abscess development. Rarely, this abscess can create a fistula tract between different structures such as the urinary bladder and the skin. Case presentation: A 86-year-old male patient with a 10-year history of laparoscopic bilateral totally extra-peritoneal (TEP) hernia repair with mesh graft presented with symptoms of watery yellow discharge from the left inguinal region. A mesh-related complication was considered. The patient’s swelling in the inguinal region was diagnosed as an abscess collection and drainage was performed. The computerized tomography of the abdomen revealed a fistula tract formation between the bladder and the skin. Discussion: The TEP hernia repair allows the surgical space to be limited to above the peritoneum and avoids entrance inside the abdomen. Although this approach was a breakthrough in the field of hernia surgery, it could lead to a few complications such as seroma development and mesh migration. Conclusion: Patients with complicated mesh infection may result in an abscess development, which can rarely create a fistula tract between different structures such as the urinary bladder and the skin. Any patient presenting with urinary tract infection symptoms with a history of a synthetic mesh should prompt clinicians to consider mesh-related complications in the differential diagnosis.